Automatic segmentation and classification of brain tumors based on multisequence MRI images with deep learning methods - Pereira, Sérgio Rafael Mano (2019)
Programa de Doutoramento em Informática (MAP-i) das Universidades do Minho, de Aveiro e do Porto